KAJIAN YURIDIS TERHADAP JAMAAH HAJI SEBAGAI KONSUMEN JASA PELAYANAN PENYELENGGARAAN IBADAH UMROH DAN HAJI PLUS BERDASARKAN UU NOMOR 8 TAHUN 1999 TENTANG PERLINDUNGAN KONSUMEN - Suyadi Suyadi (Sainteks, 2011)
Law Of Number 17 1999 With Regulation Change Had Been Law Of Number 13 2008 About Pilgrimage Organization Which Be Held By Government (Department Of Religion). In This Study, Can Be Asserted That Pilgrimage Have Been Responsible Government Because It Was National Duty. People Participation, Especially Private Party, In The Pilgrimage Organization Was A Separated Part Of Pilgrimage Organization System. This Is Significant That Private Pilgrimage Bureau Have Different Responsibility. Pilgrimage Is Consument Which Can Not Getting Loose By Law Of Number 8 1999 About Consument Protection, Particularly Consument Rights As Meritorious Service Consument Of Pilgrimage Organization. Keywords: Juridically Study, Consument, Pilgrimage.